K-BEAUTY AS AN INSTRUMENT FOR SOUTH KOREA'S NATION BRANDING IN INDONESIA - Alya Zetira Azhar; Teuku Rezasyah; Anggia Utami Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the role of K-Beauty as an instrument of South Korea’s nation branding in Indonesia during the 2018-2024 period. The analysis was conducted using Simon Anholt's Nation Brand Hexagon framework, which encompasses six dimensions: exports, culture, government, society, tourism, and investment and immigration. With a qualitative descriptive approach based on literature studies, this study show that K-Beauty is not merely a consumption trend but also a soft power instrument that supports a positive image of South Korea. In the export dimension, Korean cosmetic products are growing rapidly in the Indonesian market and have become symbols of creativity and innovation. The cultural dimension demonstrates K-Beauty's close connection to the Korean Wave, which has shaped local beauty standards. From a governance perspective, institutional support is evident through the organization of the K-Beauty Expo Indonesia and the adoption of halal certification, building South Korea's image as an adaptable nation that values ​​local values. In the people dimension, Korean celebrities as brand ambassadors strengthen emotional connections with Indonesian consumers. The tourism dimension is reflected in the increase in visits to shopping destinations like Myeong-dong and Gangnam, while the investment and immigration dimensions are demonstrated through trade agreements, the expansion of the cosmetics business, and the growing number of Indonesian students and workers in South Korea. In conclusion, K-Beauty serves as a strategic nation-branding instrument, strengthening South Korea's image while fostering socio-cultural and economic ties with Indonesia.